(In)visible Landscapes of Migration: Corporality of theImage in The Passage - Ružić, Boris; Katalinić, Marija (Contemporary Southeastern Europe, 2024)
The paper deals with a visual representation of forced migration in its specific spatial andtemporal geopolitical manifestation near the borders of Croatia from 2015 until today byfocusing on The Passage, a collection of memorial portraits of migrants who lost their livesin the bordering regions of Croatia. The text will demonstrate that forced migration canbe seen not only as an exile from one’s homeland but can also be attributed as the act ofprevention of access in a material sense (by preventing entry to a given country in searchof protection) and in a symbolic sense (by obstruction of the right to appear and assemble).This way, we see exile not as a centrifugal force of displacement but as a rhizomatic,meshed movement of potential material and visual techniques of entry and deportation.The paper will advocate those practices that help to establish migrant presence at theborders of Europe not as an aberration but as an occurrence that requires systemicchanges in power relations of representation by rearticulating imaging techniques ofmigrant (in)visibility beyond the tropes of either victimization, generalization or absence.